Kodamaea ohmeri as an Emerging Human Pathogen: A Review and Update - Zhou, Menglan; Li, Yanbing; Kudinha, Timothy; Xu, Yingchun; Liu, Zhengyin (Frontiers in Microbiology, 2021)
Background: Kodamaea ohmeri, previously known as Picha ohmeri or Yamadazyma ohmeri, has been regarded as an emerging human pathogen in recent decades and caused various types of infection with high mortality. This study systematically reviewed all the published cases of K. ohmeri infection, aiming to have a better understanding of the clinical and epidemiological characteristics of K. ohmeri infections. Methods: All the published literatures (as of 31 March 2021) among the four databases: PubMed, Embase, Web of Science, and CNKI were systematically reviewed to select appropriate studies for summarizing the demographic information, clinical and microbiology characteristics of K. ohmeri infections. Results: A total of 51 studies involving 67 patients were included for final analysis, including 49 sporadic cases and two clusters of outbreaks. Neonates and the elderly consisted of the majority of patients, and fungemia was the dominating infection type. Comorbidities (like malignancy, diabetes and rheumatism), invasive operations, previously antibiotics use and prematurity were commonly seen in patients. Sequencing and broth microdilution method were the most reliable way for the identification and antifungal susceptibility test of K. ohmeri. Amphotericin B and fluconazole were the commonest antifungal therapy strategy. The calculated mortality rates of K. ohmeri infection was higher than the common candidemia. Conclusion: Our study systematically reviewed the epidemiology, clinical characteristics, microbiology features, treatments, and outcomes of all the published cases, and call for early recognition of K. ohmeri as an emerging human pathogen in clinicians and microbiologists.